Discovery of a new species of Gonatopus (Hymenoptera: Dryinidae) from Colombia - Speranza, Stefano; Olmi, Massimo; Capradossi, Leonardo; Guglielmino, Adalgisa (Zootaxa, 2019)
Gonatopus duranprietoae sp. nov. (Hymenoptera: Dryinidae: Gonatopodinae) from Colombia is described and illustrated. This new species belongs to Gonatopus group 7. In this group, G. duranprietoae is similar to G. peruvianus Olmi, from Peru. The main difference between these two species is the shape of the metanotum: in G. duranprietoae lateral regions with two small pointed protrusions, which are absent in G. peruvianus. The key to the Neotropical species of Gonatopus group 7 is modified to include this new species.